Ehrlichia canis morulae and DNA detection in whole blood and spleen aspiration samples - Maia Faria, Joice Lara [UNESP]; Dagnone, Ana Silvia; Munhoz, Thiago Demarchi [UNESP]; Joao, Carolina Franchi [UNESP]; Biscola Pereira, Wanderson Adriano; Machado, Rosangela Zacarias [UNESP]; Tinucci-Costa, Mirela [UNESP] (Brazilian Coll Veterinary Parasitology, 2010)
The aim of this study was to compare the detection of Ehrlichta cams morulae and DNA by nPCR in whole blood and spleen aspiration The sample Included 40 dogs showing thrombocytopenia associated to clinical signs suggestive of canine ehrlichiosis Morulae detection showed that in 35 of the dogs studied, 17 had morulae in spleen tissue, and two in buffy coat smears E cants DNA was detected in 29/40 blood samples We verified that morulae detection is more efficient in cytological preparations from spleen aspiration on the other hand, nPCR on spleen and blood samples were equally efficient for disease diagnosis

O objetivo desse estudo foi comparar a pesquisa de mórulas de Ehrlichia canis e a nPCR em sangue total e em aspirado de baço. Selecionaram-se 40 cães apresentando trombocitopenia associada a sinais e sintomas sugestivos de erliquiose canina. A pesquisa de mórula mostrou que dentre 35 amostras, 17 apresentaram mórulas nas preparações do baço, e duas nos esfregaços feitos a partir da papa leucocitária. O DNA de Ehrlichia canis foi detectado em 29 de 40 amostras de baço e em 30 de 40 no sangue. No presente estudo observou-se que a pesquisa de mórula é mais eficiente nas preparações citológicas obtidas da punção aspirativa do baço e que tanto a nPCR de baço quanto a de sangue foram eficientes no diagnóstico da doença.
Detecção de mórulas e DNA de Ehrlichia canis em sangue e em aspirado de baço em cães naturalmente infectados
Keywords: Ehrlichia canis; morulae; Spleen; nPCR dogs